Distributed Cache with Utilizing Squid Proxy Server and LRU Algorithm - Abdul Ghofir; Rikip Ginanjar (Institute of Advanced Engineering and Science, 2017)
In relation to the dissemination of information, the Internet is one of the fastest media to do so. The internet’s presence is growing very swiftly and rapidly, so it has become recognized by people from all walks of life. For that, the people need the appropriate way to maintain effectiveness in the use of the Internet. The following paper describes a study of the distribution of the cache, which is performed by the squid proxy server by creating a storage network design on Linux. Cache documents that are stored in the proxy server will be distributed to another over a network storage server. The process of caching on the proxy server is using the Least Recently Used (LRU) Algorithm. This research was carried out by developing the existing method of caching server process, then it is to be added a unit as a backup storage device for the data that must be erased because of the replacement policy applied to the squid proxy server. This study is looking at how the hit ratio and byte hit ratio after adding the storage server compared to not having a storage server. At the end of this research, it is concluded that the distributed cache processes a hit ratio and byte hit ratio higher than the cache on the current proxy server.